Isomer spectroscopy of neutron-rich 168Tb103. (November 2017) - Gurgi, L.A.; Regan, P.H.; Söderström, P.-A.; Watanabe, H.; Walker, P.M.; Podolyák, Zs.; Nishimura, S.; Berry, T.A.; Doornenbal, P.; Lorusso, G.; Isobe, T.; Baba, H.; et al.
Abstract: In-flight fission of a 345 MeV per nucleon 238 U primary beam on a 2 mm thick 9 Be target has been used to produce and study the decays of a range of neutron-rich nuclei centred around the doubly mid-shell nucleus 170 Dy at the RIBF Facility, RIKEN, Japan. The produced secondary fragments of interest were identified event-by-event using the BigRIPS separator. The fragments were implanted into the WAS3ABI position sensitive silicon active stopper which allowed pixelated correlations between implants and their subsequent β -decay. Discrete γ -ray transitions emitted following decays from either metastable states or excited states populated following beta decay were identified using the 84 coaxial high-purity germanium (HPGe) detectors of the EURICA spectrometer, which was complemented by 18 additional cerium-doped lanthanum bromide (LaBr3 ) fast-timing scintillation detectors from the FATIMA collaboration. This paper presents the internal decay of a metastable isomeric excited state in the odd-odd nucleus 168 Tb, which corresponds to a single proton-neutron hole configuration in the valence maximum nucleus 170 Dy. These data represent the first information on excited states in this nucleus, which is the most neutron-rich odd-odd isotope of terbium (Z=65) studied to date. Nilsson configurations associated with an axially symmetric, prolate-deformed nucleus are proposed for the 168 Tb ground state the observed isomeric state by comparison with Blocked BCS-Nilsson calculations. Abstract : Highlights: First spectroscopy of excited states in the neutron-rich radioisotope 168 Tb. Decay gamma-rays identified using the EURICA gamma-ray spectrometer at the RIBF facility, RIKEN, Japan. Blocked BCS pairing Nilsson calculations.